Implementation Of Unplugged Coding In Physical Education Subjects At Bengkulu Mahira Nature School - Lismana, Oetari; Sumantri , Ajis; Putra , Dwinky Marta; Ardianti , Nina (CV. Generasi Insan Rafflesia, 2025)
The learning process carried out by teachers at SMP Alam Bengkulu Mahira is still too monotonous and rarely uses games in the learning process. Therefore, these learning activities seem uninteresting and students are less enthusiastic about participating in the PJOK learning process at the school. Based on the results of interviews and observations, the author was interested in providing direct socialisation to students about Unplugged Coding in PJOK lessons. The purpose of this community service by lecturers and students was to increase the learning motivation of students at Bengkulu Mahira Nature School. One of the main targets was to improve students' motor skills, learning motivation and understanding of Unplugged Coding. This action was taken so that students could be more enthusiastic, active, and focused in following the learning process provided by the teacher. In addition, they also aimed to educate students about the importance of warming up before the PJOK learning process, where in this case, the warm-up for students was in the form of a game (Coding Unplugged). Thus, the lecturers and students strive to achieve significant improvements in students' knowledge, skills, and awareness of Coding Unplugged, so that they can become caring agents of change who are ready to take action in maintaining their own health and learning motivation.